TERT promoter mutations in thyroid cancer - Michiko Matsuse; Norisato Mitsutake (Endocrine Journal)
TERT promoter mutations (TERT-p mutations) have been found in many types of cancer and have emerged to play critical roles in tumor progression. The mutations upregulate TERT transcription, and TERT not only elongates telomeres and confers unlimited proliferative capacity on tumor cells, but is also involved in tumor progression and aggressiveness. In differentiated thyroid carcinoma, TERT-p mutations are associated with a number of high-risk clinicopathological aggressiveness and worse prognosis, making it the best molecular marker to predict tumor aggressiveness so far. This review summarizes recent relevant findings regarding TERT-p mutations and their functional/mechanistic aspects.